Joint estimation of farmers' stated willingness to pay for agricultural services - Ulimwengu, John M.; Sanyal, Prabuddha (International Food Policy Research Institute, 2011)
In many developing countries, to sustain the provision of agricultural services to farmers, many have advocated the use of service fees. Successful implementation of such schemes requires understanding of determinants of farmers' willingness to pay. In this paper we use a multivariate probit approach to investigate farmers' stated willingness to pay for different agricultural services including soil fertility management, crop protection, farm management, improved produce quality /varieties, on-farm storage (post-harvest), improved individual and group marketing, and disease control. Data are from the Uganda National Household Survey 2005/2006. Controlling for individual characteristics and regional heterogeneity, our results suggest that farmers with access to information on proposed agricultural service are less willing to pay for it. Similarly, access to extension service tends to reduce farmers' willingness to pay. Market access plays also a significant role; farmers with available market are more willing to pay for agricultural services than those without available market. On the reverse, distance to the market is inversely correlated with the willingness to pay for agricultural services. The results also suggest that land ownership matters; indeed, increase in the size of land owned by farmers increases their willingness to pay for agricultural services. As expected, farmers' income, especially agricultural income significantly increases farmers' willingness to pay for agricultural services. Overall, decisions to pay or not for these services are not independent from each other implying that joint supply of these services should be recommended.